Penggunaan Media Google Classroom dan Kendalanya pada Pembelajaran Daring di Sekolah Dasar - Zidane, Jelang; Tisngati , Urip; Al Fath , Ayatullah Muhamaddin (Scholarly Journal of Elementary School, 2022)
Media plays a role in supporting the learning process, one of which is by utilizing technology as a tool in delivering learning materials. Thus, this study aims to describe how the use of Google Classroom media during online learning, obstacles, and teacher efforts in overcoming the obstacles. The qualitative descriptive research method was chosen. Teachers and students of class V SD Negeri 1 Punung as research subjects. Observation, interview and documentation techniques were used to collect data, then triangulation and data analysis were carried out. The research results obtained, namely: Google Classroom media is used by teachers to deliver material in the form of videos and files. The assignment is carried out as a learning evaluation. The obstacle is from the side of teachers and students, namely the readiness of teachers and students in carrying out online learning in order to maximize and adapt in using the features available in Google Classroom. The teacher's effort to overcome these obstacles is by sending assignment files via WhatsApp. Teachers are advised to use other media combinations that make the class more varied and interesting.